Association of TNFAIP3 gene polymorphism (rs5029939) with susceptibility and clinical phenotype of systemic lupus erythematosus - Hala Gaballah; Reham Abd-elkhalek; Ola Hussein; Shimaa Abd El-wahab (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the association of the tumor necrosis factor-alpha inducible protein 3 (TNFAIP3) (rs5029939) gene single nucleotide polymorphism (SNP) with the risk of systemic lupus erythematosus (SLE) and its clinical manifestations in a cohort of SLE patients. Patients and methods: This study included a total of 180 participants (18 males, 72 females; mean age: 30.9±10.1 years; range 17 to 59 years) including 90 SLE patients and 90 healthy controls between March 2017 and February 2020. The TNFAIP3 rs5029939 gene polymorphism was identified by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) in all participants. Results: There was a significant difference in genotype distribution of the TNFAIP3 rs5029939 SNP between SLE patients and healthy controls, where CG genotype was more common in SLE patients (53.3%) than controls (11.1%) (p=0.001). We found a significant difference in G allele frequency of TNFAIP3 (rs5029939) (37.8% with SLE vs. 5.6% with controls, p=0.001). Genotype CG was significantly associated with lupus nephritis and neuropsychiatric manifestations (p<0.05). Although the response to treatment was numerically higher with the genotype CC, it did not reach statistical significance (p=0.4). Conclusion: Our study suggests that TNFAIP3 rs5029939 gene polymorphism is associated with SLE susceptibility and may have an impact on its clinical phenotype. As such association differs among populations of diverse ethnic backgrounds, larger genome-wide association studies are warranted to further elucidate genetic associations.